Уровень технологической готовности научных разработок как фактор для принятия управленческих решений - Белан, И.И.; Левина, Д.А. (Вісник Українського матеріалознавчого товариства, 2017)
For the commercialization of scientific development it is necessary to represent at what level of readiness for implementation it is. Of particular importance is the evaluation of the level of readiness of development (PEM) acquired in the implementation of large-scale costly projects, for example, in the space or military industry. The experience of using the TRL assessment method confirms that it is an effective tool for the development of technologies, facilitating risk management, making optimal decisions regarding the financing of technologies and their transfer. Today, the use of the method of assessing the levels of readiness has become mandatory in deciding whether to finance projects for the development and transfer of technologies in various international programs. It should also be considered as one of the tools needed to manage the progress of research and development in organizations that develop new technologies.